1986
DOI: 10.1021/om00132a030
|View full text |Cite
|
Sign up to set email alerts
|

Activation of arene carbon-hydrogen bonds. Highly regioselective, electrophilic aromatic metalation with rhodium(III) porphyrin and subsequent cleavage of carbon-rhodium bond

Abstract: Octaethylporphyrmato)rhodium(III) chloride, (OEP)RhmCl, reacts with benzene in the presence of AgC104 or AgBF4 to give the phenyl-rhodium(III) complex. Anisóle, toluene, and chlorobenzene are similarly metalated exclusively at the para positions. The metalation of methyl benzoate, on the other hand, gives a 92:8 mixture of meta-and para-metalated isomers. The reactivities of arenes follow the Hammett equation with the p value of -5.43. The observed substituent effects both on reactivity and orientation unambig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…29 In this system, however, very high para selectivity is observed. This could be a result of the higher electrophilicity of the Pd(IV) center; C-H activations at Pt(IV) 30 and Rh(III) 31 give high para selectivity under kinetic conditions. 32 Figure 10.…”
Section: Resultsmentioning
confidence: 99%
“…29 In this system, however, very high para selectivity is observed. This could be a result of the higher electrophilicity of the Pd(IV) center; C-H activations at Pt(IV) 30 and Rh(III) 31 give high para selectivity under kinetic conditions. 32 Figure 10.…”
Section: Resultsmentioning
confidence: 99%
“…This result is inconsistent with electrophilic C-H bond activation, where the ρ values have been determined in the cases of PtCl 6 2-and [(OEP)RhCl] (OEP = octaethylporphyrinato). [13,14] Scheme 5. 1 H NMR analysis revealed that the kinetic isotope effect is 5.4.…”
Section: Introductionmentioning
confidence: 99%
“…The apparent two-point/one-point selectivities (K 2pt /K 1pt ) also change from 55 through 95 to 10 3 . It is impressive on the other hand, to note that the term K 2pt /(K 1pt ) 2 remains nearly constant at 10. In terms of free energy, this corresponds to the difference between one two-point adduct and two one-point adducts; …”
Section: Award Accountsmentioning
confidence: 95%
“…We elucidated the complete details of this electrophilic aromatic metallation with Hammett-type substituent correlation. 2 We then switched to acetone, which readily gave the corresponding organometallic compound 6 presumably via enolization of the ketone with Rh III as an acidic promoter and a base (formally ClO 4 ¹ ) to abstract a proton (Scheme 1). The cationic Rh III is essential as a promoter, since the chlororhodium derivative 3 shows no activity at all.…”
Section: Hostguest Systems With Convergent Multiplementioning
confidence: 99%
See 1 more Smart Citation